Primary intestinal lymphangiectasia and a review of the current literature - Altın, Zeynep; Atabay, Yusuf; Özer, Serhat; Karakoyun, Miray; Ekmekçi, Sümeyye; Yıldız Yürekli, Ezgi; Akar, Harun (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Altın Z, Atabay Y, Özer S, et al. Primary intestinal lymphangiectasia and a review of the current literature. Turk J Gastroenterol 2018; 29: 714-6.